Clinical potential of minocycline for neurodegenerative disorders - David Blum (Neurobiology of Disease, 2004)
Minocycline, an antibiotic of the tetracycline family, has been shown to display neurorestorative or neuroprotective properties in various models of neurodegenerative diseases. In particular, it has been shown to delay motor alterations, inflammation and apoptosis in models of Huntington's disease, amyotrophic lateral sclerosis and Parkinson's disease. Despite controversies about its efficacy, the relative safety and tolerability of minocycline have led to the launching of various clinical trials. The present review summarizes the available data supporting the clinical testing of minocycline for these neurodegenerative disorders. In addition, we extend our discussion to the potential applications of minocycline for combining this treatment with cellular and molecular therapy.